Inhibitory Power of Jatropha Curcas Leaf Extract on the Growth of Escherichia coli, Staphylococcus aureus, and Candida albicans Fungi - Sarah Shakina; Yusminah Hala; Mashuri Masri (Contributions of Central Research Institute for Agriculture, 2022)
This study aims to determine the effect of Jatropha curcas leaf extract on the inhibition of Escherichia coli, Staphylococcus aureus, and Candida albicans. This study was an experimental study which was arranged using a completely randomized design (CRD) consisting of 5 treatments (A0 = control (without Jatropha curcas leaf extract), A1 = 5% concentration (5 grams of Jatropha curcas leaf extract/95 ml aquadest), A2 = 10% concentration (10 grams of Jatropha leaf extract/90 ml of aquadest), A3 = 20% concentration (20 grams of Jatropha leaf extract/80 ml of aquadest), A4 = 30% concentration (30 grams of Jatropha leaf extract /70 ml of distilled water) With 3 replications with an incubation period of 24 hours and 48 hours.The parameters observed in this study were the number of clear zones (inhibitory zones) in Escherichia coli, Staphylococcus aureus, and Candida albicans, using a sliding bar. The results showed that the inhibition of Jatropha leaf extract was statistically very significant with a BNT value of a 0.01 = 0.15 and 0.13 and optimum inhibition at a concentration of 20% for Escherichia coli, for Staphylococcus aureus a BNT value of a 0.01 = 0.39 and 0.33 for optimum inhibition at a concentration of 20%, BNT a value of 0.01 = 0.52 and 0.29 for Candida albicans and optimum inhibition at a concentration of 30%.